Treatment of AKI in developing and developed countries: An international survey of pediatric dialysis modalities - Raina, Rupesh (PLoS One, 2017)
HYPOTHESIS: Acute kidney injury (AKI) is a common cause of morbidity and mortality worldwide, with a pediatric incidence ranging from 19.3% to 24.1%. Treatment of pediatric AKI is a source of debate in varying geographical regions. Currently CRRT is the treatment for pediatric AKI, but limitations due to cost and accessibility force use of adult equipment and other therapeutic options such as peritoneal dialysis (PD) and hemodialysis (HD). It was hypothesized that more cost-effective measures would likely be used in developing countries due to lesser resource availability. METHODS: A 26-question internet-based survey was distributed to 650 pediatric Nephrologists. There was a response rate of 34.3% (223 responses). The survey was distributed via pedneph and pcrrt email servers, inquiring about demographics, technology, resources, pediatric-specific supplies, and preference in renal replacement therapy (RRT) in pediatric AKI. The main method of analysis was to compare responses about treatments between nephrologists in developed countries and nephrologists in developing countries using difference-of-proportions tests. RESULTS: PD was available in all centers surveyed, while HD was available in 85.1% and 54.1% (p = 0.00), CRRT was available in 60% and 33.3% (p = 0.001), and SLED was available in 20% and 25% (p = 0.45) centers of developed and developing world respectively. In developing countries, 68.5% (p = 0.000) of physicians preferred PD to costlier therapies, while in developed countries it was found that physicians favored HD (72%, p = 0.00) or CRRT (24%, p = 0.041) in infants. CONCLUSIONS: Lack of availability of resources, trained physicians and funds often preclude standards of care in developing countries, and there is much development needed in terms of meeting higher global standards for treating pediatric AKI patients. PD remains the main modality of choice for treatment of AKI in infants in developing world.